Factors Effecting the Effectiveness of AIS “SAKTI” Based on Delone and Mclean (2003) Modified Models (E-Jurnal Akuntansi, 2026)
The aim of this research is to empirically test the impact ofsystem quality, information quality, management support on theperceived usefulness, user satisfaction and the effectiveness ofaccounting information systems (AIS). The sample was used by143 respondents from SAKTI users in the Sidoarjo Mud ControlCenter, the Brantas River Region Hall, and the East Java NationalRoad Implementation Hall-Bali Ministry of PUPR. This researchuses primary data obtained from the questionnaire. Datacollection techniques using convenience sampling and dataanalysis techniques using SEM-PLS. Results of system qualityanalysis do not affect user satisfaction, information quality doesnot affect usefulness, system quality affects usefulness, qualityof information affects user satisfactions, management supportaffects customer satisfaction and usefulness, usefulness affectsuser satisfactions and the effectiveness of AIS, user satisfactionsaffects the effectiveness of AIS. Implications of this research arethe development of models to measure the effectiveness of AISand also as a reference for improvements in SAKTI applicationslater on.
Keywords: Effectiveness of AIS; ISSM Deloine and Mclean; Management Support; Mandatory